2016
DOI: 10.3390/ma9060466
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally-Friendly Dense and Porous Geopolymers Using Fly Ash and Rice Husk Ash as Raw Materials

Abstract: This paper assesses the feasibility of two industrial wastes, fly ash (FA) and rice husk ash (RHA), as raw materials for the production of geopolymeric pastes. Three typologies of samples were thus produced: (i) halloysite activated with potassium hydroxide and nanosilica, used as the reference sample (HL-S); (ii) halloysite activated with rice husk ash dissolved into KOH solution (HL-R); (iii) FA activated with the alkaline solution realized with the rice husk ash (FA-R). Dense and porous samples were produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 49 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…There exist only a relatively small number of studies on the utilisation of RHA as a precursor for the production of AAB. RHA was blended with other precursors such as fly ash (Detphan and Chindaprasirt, 2009;Hwang and Huynh, 2015;Ziegler et al, 2016), calcined water treatment sludge (Nimwinya et al, 2016), slag and palm oil fuel ash (Karim et al, 2013), slag and fly ash (Karim et al, 2015), slag (Suksiripattanapong et al, 2017), or red mud (He et al, 2013). Research results confirmed the reactivity of RHA in an alkaline environment as a Si donor.…”
Section: Introductionmentioning
confidence: 70%
“…There exist only a relatively small number of studies on the utilisation of RHA as a precursor for the production of AAB. RHA was blended with other precursors such as fly ash (Detphan and Chindaprasirt, 2009;Hwang and Huynh, 2015;Ziegler et al, 2016), calcined water treatment sludge (Nimwinya et al, 2016), slag and palm oil fuel ash (Karim et al, 2013), slag and fly ash (Karim et al, 2015), slag (Suksiripattanapong et al, 2017), or red mud (He et al, 2013). Research results confirmed the reactivity of RHA in an alkaline environment as a Si donor.…”
Section: Introductionmentioning
confidence: 70%
“…Compared with other industrial fields, the use of amorphous RHA silica in the production of concrete can realize large-scale consumption and reuse of waste, and hence eventually reduces the environmental impact due to improper disposal and land occupation. RHA is economical, widely available and highly reactive as a supplementary cementing material, due to its excellent physically filling and chemically pozzolanic effects [ 18 , 19 , 20 , 21 , 22 ]. It is also a promising substitute for replacing silica fume (SF) in high-performance concrete production.…”
Section: Introductionmentioning
confidence: 99%
“…The porous geopolimer-type compositions were produced using the rice hulls ash with aluminum powder as a foaming agent [20]. Addition of aluminum powder to the composition increases the porosity and decreases the density of the material.…”
Section: Discussionmentioning
confidence: 99%